Analysis of sliding mechanics force degradation during postextraction space closure - Umićević-Davidović Mirjana; Arapović-Savić Marijana; Arbutina Adriana; Adamović Tijana; Kuzmanović-Radman Irena (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction Due to its simplicity, sliding mechanism is very often used in clinical practice for post-extraction space closure, however, the efficiency of this method may be reduced due to friction and changes in the properties of the materials used in this method. The most commonly used methods of sliding mechanics are nickel titanium (NiTi) closed coil spring and elastic chain. The aim of this study was to analyze force degradation in the application of nickel titanium closed coil springs and elastic chains during post-extraction space closure within treatment with fixed orthodontic appliances. Material and Methods The total sample in this study consisted of 78 post-extraction spaces in patients who were indicated for extraction of first premolars and treatment with fixed orthodontic appliances. Nickel titanium closed coil springs and elastic chains were used to close the post-extraction spaces. Post-extraction spaces were monitored for 6 months with follow up examinations every 4 weeks. Measurements of initial force, at the beginning of mechanism activation and residual force in the observation period were performed during control examinations. Results Results of this research showed that with both methods of sliding mechanism there was a significant decrease in the observation period. When using NiTi closed coil springs, the value of average initial force at control examination was between 189.00-210.25 g, while residual was in the range of 117.56-133.50 g that NiTi closed coil springs kept an average 61.57% of initial force. The average initial force on the control examinations for elastic chains was between 184.5-205.38 g, while residual force was in range of 100.39-113.00 g, that elastic chains retained an average 53.41% of initial force. Conclusion There was a significant force degradation between inspections, when sliding mechanics were applied. The loss of force between activation phases of NiTi closed coil springs was smaller compared to the forces produced by elastic chains.